Question Number 104696 by nimnim last updated on 23/Jul/20

Answered by Rasheed.Sindhi last updated on 23/Jul/20

A′s age at present x years  B′s age at present y years      x−7= 5(y−7)^2 .......(i)     y+3=(2/5)(x+3).........(ii)  (ii)⇒  x=(5/2)(y+3)−3                  =((5y+9)/2)  (i)⇒((5y+9)/2)−7=5(y^2 −14y+49)            5y+9−14=10y^2 −140y+490           10y^2 −145y+495=0           2y^2 −29y+99=0         y=((29±(√(841−792)))/4)         y=((29±7)/4)=9,5(1/2)^(×)   5(1/2) is false,because 7 years ago  the age be negative.Negative  age is not acceptable.  y=9:x=((5(9)+9)/2)=27  A′s age=27 years  B′s age= 9 years

Commented by1549442205PVT last updated on 23/Jul/20

Solve quadratic equation false  applying root formular y=((b±(√Δ))/(2a))  a=2⇒2a=4!

Commented byRasheed.Sindhi last updated on 23/Jul/20

Thank you sir.I′m going to  correct it.

Commented bynimnim last updated on 23/Jul/20

Thank you Sir.